Defining the wrestler`s body - Appropriate measures for targeting weight class - Groth, B.; Foote, D. M.; Horswill, C. A. (International Journal of Wrestling Science, 2018)
Competition within a specified weight class is a fixture in the sport of wrestling to help prevent injury and allow equal opportunity among participants. Weight reduction to a lower than normal weight class is a common practice in the U.S. Because of adverse events with such practice, national governing bodies (NGB) in the states have established programs to guide wrestlers to safe weight classes based on body composition. For large teams of participants, the field assessments adopted by NGB`s include anthropometry using skinfold thicknesses (SF) and bioelectrical impedance analysis (BIA) because of the validation testing and efficiency. The standard used to calibrate, or cross validate SF, BIA, and any other field methods has most often been densitometry that typically relies on hydrostatic weighing of the athlete (HW). Assumptions on which HW was developed include fixed constants for hydration and mineralization of the fat-free body. However, maturation level, gender, and ethnicity will alter these constants and leave densitometry to be erroneous regardless of whether HW or other methods (air displacement plethysmography) are applied as the validation standard. The biological variability of the wrestler body must be accounted for to develop accurate and reliable methods. In this way, fair and safe minimal weight programs can be implemented in the sport.